Reflections on the State: the tensions and affinities between the thoughts of Louis Althusser and Pierre Bourdieu (Revista da Faculdade de Direito, Universidade de São Paulo, 2023)
This paper intends to analyze the tensions and affinities between Louis Althusser’s and Pierre Bourdieu’s reflections on the State. In order to do so, firstly, it focuses on the general aspects of Louis Althusser’s thought that support his understanding of the State as an instrument of class domination to, from there, analyze the Althusserian theory of the “ideological State apparatuses” (ISA). It then concisely addresses the concepts of field, capital and habitus, as defined by Pierre Bourdieu, and then examines his thesis about the State as an institution responsible for the (re)production and canonization of forms of social classification.